Ideal Madrasah Diniyah Takmiliyah Leadership Strategy - Qurtubi, Ahmad; Muslihah, Eneng; Romli, Ombi; Muttaqin, Zainal; Herianto, Ii Puji (Indonesian Journal of Advanced Research, 2024)
To examine the optimal leadership approach of Madrasah Diniyah Takmiliyah, this study uses a qualitative methodology through literature review. Literature reviews from various sources of books, scientific publications, and scientific journals, as well as the results of interviews with specialists relevant to leadership at Madrasah Diniyah Takmiliyah, are the source of data for this research. The findings are as follows: 1) A number of elements, such as leadership style, members' desires and desires, internal and external influences, and self-development, affect how effective leadership is in Madrasah Diniyah Takmiliyah. 2) According to research, madrasah leaders with an adaptive leadership style can adapt to the environment and the demands of their students. These methods include the development of efficient communication, the improvement of joint competence, the implementation of joint activities, the provision of feedback, and the creation of a supportive environment.